The Impact of Population Factors on Economic Growth of Bangka Belitung Islands - Indonesia - Sapitri, Ayu (Jurnal Ilmu Ekonomi Terapan, 2021)
This study aims to analyze and determine the effect of population factors on economic growth in the Province of the Bangka Belitung Islands. The analysis method used is panel data regression. The type of data is quantitative data in the form of ADHK GRDP data by Regency/City, population growth rate, labor force participation rate, average length of schooling and life expectancy from 2010-2019. The data source is secondary obtained from the Central Bureau of Statistics of the Bangka Belitung Islands Province. The results showed that the population growth rate had a negative and significant effect on economic growth while the labor force participation rate had a positive and insignificant effect on economic growth, the average length of schooling had a positive and significant effect on economic growth and life expectancy had a positive and significant effect on growth. the economy of the Bangka Belitung Islands Province. Simultaneously the population growth rate, labor force participation rate, average length of schooling and life expectancy have a positive and significant impact on economic growth in the Province of the Bangka Belitung Islands. Keywords: Economic Growth, Population Growth Rate, Labor Force Participation Rate, Average Length of Schooling, Life Expectancy. JEL :  O40, J11, J21, P36